2021
DOI: 10.21203/rs.3.rs-126892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Federated Learning used for predicting outcomes in SARS-COV-2 patients

Abstract: ‘Federated Learning’ (FL) is a method to train Artificial Intelligence (AI) models with data from multiple sources while maintaining anonymity of the data thus removing many barriers to data sharing. During the SARS-COV-2 pandemic, 20 institutes collaborated on a healthcare FL study to predict future oxygen requirements of infected patients using inputs of vital signs, laboratory data, and chest x-rays, constituting the “EXAM” (EMR CXR AI Model) model. EXAM achieved an average Area Under the Curve (AUC) of ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…Thus, a multitude of AI approaches have been developed, published and indicated great potential for clinical support, but they were often overfit, being trained using proprietary data or from a single site [14][15][16][17][18][19] . Alternatively, federated approaches allow algorithms to access data from multiple sites without the need of sharing raw data, but through this paradigm access is granted to a single algorithm and consortium, with sharing of model weights instead of raw data 20,21 . In particular, deep neural networks were used for the identification and segmentation of abnormal lung regions affected by SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a multitude of AI approaches have been developed, published and indicated great potential for clinical support, but they were often overfit, being trained using proprietary data or from a single site [14][15][16][17][18][19] . Alternatively, federated approaches allow algorithms to access data from multiple sites without the need of sharing raw data, but through this paradigm access is granted to a single algorithm and consortium, with sharing of model weights instead of raw data 20,21 . In particular, deep neural networks were used for the identification and segmentation of abnormal lung regions affected by SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Both, FL as well as the more superordinate setting of distributed ML are used in many applications where labels can contain highly sensitive information. For example, in the medical sector, hospitals employ distributed learning to collaboratively build ML models for disease diagnosis and prediction [11,17]. In some cases, the medical data is collected directly from the patients' personal devices [8], e.g., mobile phones [9], where an application of FL could introduce many potential benefits.…”
Section: Introductionmentioning
confidence: 99%
“…FL avoids the need to collect and store private data at a centralized location by allowing institutions to download a preliminary ML model, refine it locally, and then upload updated model parameters to an aggregator. [5][6][7] FL models have been utilized to identify COVID-19 through computed tomography scans and to predict clinical outcomes in COVID-19 patients -published reports indicate that FL models not only outperform those trained on single-institution data but also approach the performance of traditional ML models trained on data pooled from multiple institutions. 6,[8][9][10] COVID-19 has diverse clinical manifestations, and a common complication in hospitalized COVID-19 patients is acute kidney injury (AKI).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] FL models have been utilized to identify COVID-19 through computed tomography scans and to predict clinical outcomes in COVID-19 patients -published reports indicate that FL models not only outperform those trained on single-institution data but also approach the performance of traditional ML models trained on data pooled from multiple institutions. 6,[8][9][10] COVID-19 has diverse clinical manifestations, and a common complication in hospitalized COVID-19 patients is acute kidney injury (AKI). [11][12][13][14] Studies have reported AKI prevalence up to 46%, and mortality rates in AKI cohorts vary from 35%-71%.…”
Section: Introductionmentioning
confidence: 99%